Lazisnu's Role in Social Life During The Covid-19 Pandemic - Muttaqin, M Khoirul; Basyirah, Luthfiana; Surur, Miftachus (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2022)
This study aims to determine the role of Lazisnu in social life during the Covid-19 pandemic. The research method used in this research is a qualitative approach with the type of case study research. The data sources used are primary and secondary data sources obtained from observations, interviews, and documentation. The informants in this study consisted of 23 informants, namely the chairman, secretary, treasurer, and 20 mustahiq recipients of assistance from Lazisnu Sendangagung. Then the data that has been obtained is analyzed through several stages of data reduction, data presentation, and conclusion. The results show that the innovation of the Lazisnu program can be felt by the village community with a high level of objectivity and actuality in social life accompanied by a sense of brotherhood, unity, and independence, and not to forget solid religious symbols through awareness for zakat, infaq, and shodaqoh. This research implies that it is expected to be a suggestion for institutions to continue to develop existing programs. In addition, the limitations in this study were only conducted on one Lazisnu, and the informants in this study were limited, so it is hoped that future research can explore Lazisnu in East Java so that information related to Zizwaf management is more comprehensive.